The right to parody?: a comparative analysis - Jacques, Sabine (2016)
Copyright law grants exclusive rights to right-holders which prevent others from exploiting copyright-protected works without authorisation. However, this right is not absolute. Legislation includes specific exceptions which preclude right-holders from exercising their prerogatives in particular cases which foster creativity and cultural diversity within that society. The parody exception pertains to this ultimate objective by permitting users to reproduce copyright-protected materials for the purpose of parody. While the parody exception is not harmonised at international level, the EU Information Society Directive offers EU Member States the option of including a parody exception within national copyright legislation as part of a harmonising framework. The UK took advantage of this option, and introduced a new copyright exception for parody in October 2014. To understand the meaning and scope of the new exception in UK copyright law and to analyse whether EU harmonisation of the parody exception is achievable, this thesis examines and compares four jurisdictions which differ in their protection of parodies: France, Australia, Canada and the United Kingdom. This thesis is concerned with finding an appropriate balance between the protection afforded to right-holders and the public interest in encouraging parody. This is achieved by analysing the parody exception to the economic rights of right-holders, the application of moral rights and the interaction of the parody exception with contract law. As parodies constitute an artistic expression protected under the right to freedom of expression, this thesis considers the influence of freedom of expression on the interpretation of this specific copyright exception. Furthermore, this thesis aims to provide guidance on how to resolve conflicts where fundamental rights are in conflict.